Estudo do potencial de diferenciação de células-tronco mesenquimais equinas oriundas do sangue da medula óssea cultivadas sobre um filme multicamadas de biopolímeros: quitosna, HA e CMC - Listoni, Amanda Jeronimo [UNESP] (2013)
Stem Cell therapy is currently experiencing its moment of maximum visibility. All this attention is given the fact that this procedure is a potential target in the treatment of serious diseases. The wide applicability of therapy with stem cells is possible due to your unlimited potential to differentiate into several cell lineages, as well as their capacity for self-renewal. For this technique can be used in the repair of fractures or healing of various tissues can be performed in combination with biomaterial, which have a potential merger of cellular and assist in tissue regeneration, and after accession in their place of action, this technique is called Biocure and diverse substrates can be used in this way was chosen a biomaterial Chitosan, which comes from a raw material known as chitin, an abundant polymer in nature, which has recently been tested as Biocure. In our tests, we noticed that these biomembranes accelerate the process of cell adhesion and cell growth have a constant, so a great option in the surgical therapy